Case Report: Myeloid neoplasms with the t(3;12)(q26.2;p13.1)/MECOM-ETV6 translocation: report of two new cases and review of the literature - Mikkilineni, Soumya; Pineda-Reyes, Juan Pablo; Wilde, Lindsay; Ferber, Andres; Wang, Zi-Xuan; Peiper, Stephen; Uppal, Guldeep; Gong, Jerald; Liu, Jinglan (Frontiers in Oncology, 2025)
The MECOM (MDS1 and EVI1 complex locus) gene, located at 3q26.2, encodes an oncogenic transcription factor implicated in multiple signaling pathways. Rearrangements involving MECOM/3q26.2, including inversions, translocations, insertions and cryptic chromosomal changes, are observed in myeloid neoplasms and are associated with high-risk disease features and poor clinical outcomes. The translocation t(3;12)(q26.2;p13.1) is a rare genetic event, resulting in a fusion of the MECOM gene at 3q26.2 with the ETV6 gene at 12p13.1. To date, only 78 cases of hematologic neoplasms harboring t(3;12) have been reported in the English literature, primarily as case reports or case series. T(3;12) has been associated with abnormalities of chromosome 7, multiple hematopoietic lineage dysplasia, and poor prognosis. Given its rarity, studies on t(3;12) in myeloid neoplasms are limited. In this report, we present two additional cases exhibiting t(3;12), initially identified through routine karyotyping. The clinicopathological, cytogenetic and molecular genetic characteristics were summarized and discussed. A comprehensive review of partner genomic loci and genes mutated in myeloid neoplasms with MECOM rearrangement was conducted. The AF4 gene and the transcription elongation control pathways are proposed as potential therapeutic targets for MECOM-rearranged myeloid neoplasms.